IMPLEMENTASI KEBIJAKAN PENYELESAIAN SENGKETA PERTANAHAN MELALUI MEDIASI DI KANTOR PERTANAHAN KOTA SURAKARTA - Sri Suharsih (JI@P, 2017)
Sri Suharsih, 2016. “Implementation of Land Dispute Resolulation Policythrough Mediation in Land Office of Surakarta Urban Government”. SlametRiyadi University Surakarta, Thesis, unpublished.This research objective was to describe the land dispute resolution throughmediation at Land Office in Surakarta Urban Government. Descriptivequalitative research strategy was used in this study to approach the researchobjectives. The respondents were selected on the basis of purposivesampling. In doing so, the respondents were Land Office officers, those whowere disputes, and the community members.The data was collected by usinginterview technique and document study as well. Research results indicatedthat dispute resolutions were solved according to the existing regulations. Thefulfilled element in dispute resolution was through the mediation.Implementation of the Goverment Regulation number 3 the year of 2011 onthe Management, Investigation and Handling on the Land Cases analysedaccording to Edward III theory, discovered that there were four interrelatedvariables. Those four variables were communication, human resource,disposition, and bureaucratic structure. Research results indicated thatcommunication variable effectively worked between the facilitator or mediatoron the one hand and those who disputed. Dealing with the human resource,research result showed that although there was lack of man power, but theexisting limited qualified staffs were competent to do their duties and theywere also able to finish their duties according to timeline. Implementer ofdisposition implemented the activities according to the Surakarta UrbanGovernment Land Office’ guidance. Related to bureaucratic structure,research result showed that the bureaucratic stucture contributed a lot insucceeding the policy implementation. The obstacles that the implementorsfaced was the time constraint to resolve the disputes through mediation sincethey have to make mutual aggreement between both who were in the situationof conflict. In this case, the mediators had no authority to decide.Key words: Communication; human resource; disposition; bureaucratic structure;disputes; mediation.1. Pendahuluan